Certain considerations in pricing unbundled transmission services - Hassan, M. Y.; Majid, M. S.; Hussin, F.; Rahman, Hasimah Ab.; Lo, K. L. (2006)
In deregulated environment, the transmission network is considered to be the key factor of the electricity markets. One of the important issues in this context is how to charge the users for the use of transmission facilities in the fair way and at the same time allowing the transmission utilities to recover their transmission costs. Several methodologies have been developed to recover the cost of transmission services and to estimate the power contributed by single generating unit in lines and loads. Both developed methods attempt to allocate the charge of the use of the transmission system. This paper describes certain aspects to be considered in pricing the unbundled transmission services. These aspects cover the type of transmission services, the costs related to the services and the methods used to calculate the costs of transmission services. This paper also proposes a new approach to allocate the costs of the transmission services among the transmission user utilising the properties of MW-mile based method. A case study based on a 6-bus system is used to highlight the merit of the proposed approach over the existing approaches. The case study results show that the proposed approach provides a better economic signal in allocating the charges to the transmission user.